Analisis Pengaruh E-Service Quality, E-Word Of Mouth, serta Promotion dan Ads Terhadap Loyalitas Konsumen di Marketplace - Sadeli, Deva Ismaya; Aritonang, Y. M. Kinley (Universitas Katolik Parahyangan, 2024)
The trend of digital-based transactions continues to increase along with the implementation of social restrictions during the pandemic, even it becomes a new habit for the millennial generation after the pandemic ends. In Southeast Asia, Indonesia was the first rank for the retail sales through e-commerce in 2021. The competition among e-commerce, especially the marketplaces in Indonesia has become very tight. Customer satisfaction, trust and loyalty are the important indicators for improving marketplace performance. In this research, there are three main factors that are further investigated for their influence on customer satisfaction, trust, and loyalty namely e-service quality, e-word of mouth along with promotion and ads. The research was conducted on 162 Tokopedia user with the majority of the millennial generation. Hypothesis testing was carried out using the partial least square structural equation (PLS-SEM) technique. The results of this study indicate that e-service quality has a significant effect on loyalty through satisfaction and trust, promotion and ads has a significant effect on loyalty through satisfaction, and e-word of mouth has no significant effect on satisfaction, trust and consumer loyalty. To get consumer loyalty, the marketplace can improve e-service quality which has the most significant effect followed by promotion and ads.